Questioning the role of puppet masters today - Jungkung Setyo Utomo; Sugeng Nugroho; Aris Setiawan (Universitas Sultan Ageng Tirtayasa, 2024)
The development of the times has brought significant changes in various aspects of life, including traditional arts. One of the traditional arts that still exists and is undergoing transformation is shadow puppetry. The puppeteer, as the leader of the wayang kulit performance, has a central role in maintaining the continuity and relevance of this art. This research aims to document and analyze the role of shadow puppet puppeteers in the current cultural and social context. The research methods used were participatory observation and in-depth interviews with several active puppeteers. Research findings reveal that the role of the puppeteer is not only limited to presenting traditional stories, but also involves adaptation to contemporary realities. Modern puppeteers are faced with the challenge of maintaining the authenticity of the art of shadow puppetry while meeting the expectations and interests of today's audiences. Apart from that, the role of the puppeteer also involves educational and cultural preservation functions. The puppeteer acts as an intellectual leader who is able to convey moral and social messages through wayang stories. They are also involved in educating the younger generation about traditional values and cultural history through wayang performances. The results of this research provide in-depth insight into the role of shadow puppet puppeteers in a modern context. The sustainability of this art not only depends on maintaining tradition, but also on the ability of the puppeteer to adapt to the dynamics of the times. Therefore, this research makes an important contribution in understanding how traditional arts such as shadow puppetry can remain relevant and develop in the contemporary era